2019
DOI: 10.1108/ijoes-12-2018-0185
|View full text |Cite
|
Sign up to set email alerts
|

Crypto-currencies narrated on tweets: a sentiment analysis approach

Abstract: Purpose Crypto-currencies, decentralized electronic currencies systems, denote a radical change in financial exchange and economy environment. Consequently, it would be attractive for designers and policy-makers in this area to make out what social media users think about them on Twitter. The purpose of this study is to investigate the social opinions about different kinds of crypto-currencies and tune the best-customized classification technique to categorize the tweets based on sentiments. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Similarly, Sattarov – (2020) obtain 0.62 accuracy when predicting BTC price using sentiment analysis. Overall, the superiority of the SVM forecast is in line with previous studies which support SVM’s, such as Ismail et al (2020), Rouhani and Abedin (2020) and Mallqui and Fernandes (2019).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, Sattarov – (2020) obtain 0.62 accuracy when predicting BTC price using sentiment analysis. Overall, the superiority of the SVM forecast is in line with previous studies which support SVM’s, such as Ismail et al (2020), Rouhani and Abedin (2020) and Mallqui and Fernandes (2019).…”
Section: Resultssupporting
confidence: 88%
“…Lamon et al (2017) found logistic regression to perform best in using tweets to predict 44% of price increases and 62% of price falls. Likewise, Rouhani and Abedin (2020) found that more than 50% of positive beliefs about cryptos with the SVM outperform other ML classifiers. Last, but not least, Mai et al (2018) reported that social media sentiment is an important predictor to determine BTC's price, with, however varying impact of social media information.…”
Section: Sentiment Analysis Cryptocurrency and Machine Learningmentioning
confidence: 95%
“…Also, through sentiment analysis in Abraham et al (2018), it is shown that the tweet sentiments are highly correlated with cryptocurrency price movements. In a similar study, Rouhani & Abedin (2019) show that Ripple has the highest percentage of positive tweets (52%), and Bitcoin receives the highest percentage of negative tweets (27%) among all the cryptocurrencies by analysing around five million tweets. The predictive power of social media sentiment analysis is studied in Kraaijeveld & De Smedt (2020) and Kim et al (2021), and it is shown that Twitter sentiment has predictive power for price returns of Bitcoin, Bitcoin Cash, and Litecoin, and cryptocurrency markets are more responsive to positive social sentiment when it is in a downward trend.…”
Section: Related Literaturementioning
confidence: 82%
“…Identification of the most impactful tweets through metrics such as retweets, comments, and high impact authors. Several authors have performed social media analysis in relation with citizen and financial market expectations, identifying the topics citizens were most interested in, based on the number of retweets (Romelli et al, 2022), doing Twitter sentiment analysis on cryptocurrencies (Rouhani & Abedin, 2019) or performing a literature review of the capacity of Twitter as an analytical and prognostic platform (Cano-Marin et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Several research studies exist on digital currencies and sentiment analysis of digital currencies on social media: machine learning techniques were employed, to demonstrate through empirical evidence that the use of combined Twitter data is valuable in forecasting the cryptocurrency volatility, return on investment and trading volume, with a particular emphasis on Bitcoin (Shen et al, 2019). Research has been performed on sentiment analysis to study cryptocurrencies from Twitter data and classify tweets as positive, neutral and negative, with the purpose of identifying pattern and pattern changes in public sentiment about cryptocurrencies, adding to the literature on how public perceptions and citizen sentiment about cryptocurrencies can be shaped (Rouhani & Abedin, 2019).…”
Section: Digital Currencies and Sentiment Analysismentioning
confidence: 99%